ESTADO NUTRICIONAL MATERNO E RESULTADOS PERINATAIS ADVERSOS EM GESTAÇÕES COM PRÉ-ECLÂMPSIA - Silva, Maria Gracyella Ferreira da; Santos, Rayssa Hellen Souza dos; Gomes, Thaynara Roberto da Silva; Ferreira, Raphaela Costa; Oliveira, Alane Cabral Menezes de (Gep News, 2019)
Trabalho apresentado durante o I MASMI